Turkey's accession to the EU: What will the Common Agricultural Policy cost? - Harald Grethe (Humboldt-Universität zu Berlin, Wirtschafts- und Sozialwissenschaften an der Landwirtschaftlich-Gärtnerischen Fakultät, 2004)
At the EU Council in December 2004, European heads of governments will decide on a potential date for the start of EU accession negotiations with Turkey. Various recent analyses assess the cost of applying the Common Agricultural Policy of the EU (CAP) to Turkey without taking into account the specific structure of the agricultural sector in Turkey, which would determine the receipts from EU funds. This paper assesses potential budgetary effects resulting from the application of the CAP to Turkey, if Turkey should accede in 2014. The analysis is based on macroeconomic projections from the literature, equilibrium modelling of the Turkish agricultural sector, and projections of the future development of the CAP. It is found that total EU budgetary outlays for the application of the CAP to Turkey could total about 3.3 billion in 2014 and rise to 5 billion in 2024 due to full phasing in of direct payments and rural development policies. The resulting net transfer under the CAP to Turkey would be about 1.6 billion in 2014 and could increase to 2.6 billion in 2024. Such sums take a backseat to projected transfers under the structural policy of the EU and the overall political project of including Turkey in the EU. – – Im Dezember 2004 wird der Europäische Rat über die Festlegung eines Zeitpunkts zur Aufnahme von Beitrittsverhandlungen mit der Türkei entscheiden. Die Diskussion über die aus der Gemeinsamen Agrarpolitik der EU (GAP) resultierenden Budgetwirkungen eines EUBeitritts basiert bisher meist auf Schätzungen, die die spezifische Struktur des türkischen Agrarsektors sowie zukünftige Änderungen der GAP bis zu einem Beitritt der Türkei kaum einbeziehen. In diesem Beitrag werden die aus der GAP resultierenden Budgetwirkungen eines potentiellen EU-Beitritts der Türkei im Jahr 2014 auf Grundlage der Literatur entnommener makroökonomischer Projektionen, Abschätzungen zukünftiger Änderungen der GAP sowie einem Gleichgewichtsmodell des türkischen grarsektors analysiert. Im Ergebnis ergeben sich EU-Zahlungen an die Türkei im Rahmen der GAP von insgesamt 3,3 Mrd. im Jahr 2014, die nach einer schrittweisen Einführung des vollen Umfangs der GAP im Jahre 2024 etwa 5 Mrd. betragen. Der sich aus der GAP potentiell ergebende Netto-Transfer aus dem EU-Budget an die Türkei beträgt 1,6 Mrd. im Jahr 2014 und steigt bis 2024 auf etwa 2,6 Mrd. an. Im Verhältnis zu den sich voraussichtlich aus der europäischen Strukturpolitik ergebenden Transfers und dem politischen Gesamtvorhaben einer Integration der Türkei sind diese Summen eher unbedeutend.
Keywords: 330; Turkey; EU accession; CAP; budgetary effects; Türkei; EU-Beitritt; Gemeinsame Agrarpolitik; Budgetwirkungen